Relationship Between Mental Toughness and Competitive Anxiety in Kabaddi Athletes in Central Java - Ericca Putri Andani; Said Junaidi (Journal of Physical Education Health and Sport, 2025)
The physical performance of Kabaddi players is not simply determined by physical skills, but also by their mental preparedness for dealing with competitive stress. Perhaps competitive anxiety is experienced prior to and/or during competition and interferes with focus and performance. On the other hand, psychological resilience is instrumental in enabling athletes to maintain focus, confidence and pressure regulation. there has been less such data available for this parameter on Kabaddi athletes. The present study intends to examine the relationship between mental toughness with competitive anxiety of Kabaddi athletes in Central Java Province. This study used a quantitative correlational design. The research sample consisted of 24 Kabaddi athletes in Central Java Province, selected using a total sampling technique. Two measurement instruments, the Sports Mental Toughness Questionnaire (SMTQ) and the Sports Competitive Anxiety Test(S CAT), were used to gather data. statistical analysis methods:tests for normality and linearity, t:ests I;or correlation based on the Pearson Product-Moment~ 1. The test of correlation results indicated that mental toughness was negatively and significantly related to competitive anxiety (r = –0.517; p = 0.010). This means that the higher the level of mental toughness, the lower the level of competitive anxiety experienced by athletes. The normality test also showed that both variables were normally distributed, and the linearity test results showed a linear relationship between the two. Mental toughness plays an important role in reducing competitive anxiety among Kabaddi athletes. Higher mental toughness helps athletes stay focused, calm, and confident in the face of competitive pressure. The results of this study can be used as a basis for coaches in designing psychological training programs to improve athlete performance.